The Ecofeminism Practice: The Women's Movement in the Documentary Film “Sangihe Melawan” - Khairiyah, Alfiatul; Muryani, Tri; Isnania, Rahma (Jurnal Pemikiran Sosiologi, 2024)
Ecofeminism is an interrelated and holistic theory and practice. Ecology, in conjunction with discourses on women's freedom and radical democracy, constitutes one of the primary pillars of democratic confederalism, which is the development of the political paradigm in Indonesia. Ecofeminism also manifests in several areas, including the women's resistance movement against gold mining by PT Tambang Mas Sangihe (TMS) in Sangihe. This study aims to describe the representation of the women's movement in the documentary film "Sangihe Melawan," which was uploaded to the YouTube channel of Watchdoc Documentary on July 1, 2022. This research employs semiotics techniques. The data analysis unit in this study includes images or visuals, audio (dialogue and narration), acting, setting, type of shot, and angle, which collectively demonstrate the role of women in the concept of Social Ecofeminism. The results indicate that women are represented as the most disadvantaged parties in the exploitation of natural resources. The women's movement to protect the environment is also depicted as an effortful endeavor. The women's resistance to the expansion of gold mining in Sangihe was manifested in various actions, including awareness-raising activities, a women's rally, legal action against PT TMS through the Manado and Jakarta Administrative Courts, and other legal avenues.